2010
DOI: 10.1111/j.1439-0507.2010.01883.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Pga1, a putative Candida albicans cell wall protein necessary for proper adhesion and biofilm formation

Abstract: The fungal pathogen Candida albicans is a leading causative agent of death in immunocompromised individuals. Many factors have been implicated in virulence including filamentation-inducing transcription factors, adhesins, lipases and proteases. Many of these factors are glycosylphosphatidylinositol-anchored cell surface antigenic determinant proteins. Pga1 is one such protein shown to be upregulated during cell wall regeneration. The purpose of this study was to characterise the role Pga1 plays by creating a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…The GPI7-null mutant showed reduced hyphal growth on solid media, increased sensitivity to Calcofluor white (CFW), reduced virulence in mice, and lytic action of macrophages (50). The PGA1 mutant showed reduced adherence and biofilm formation and increased sensitivity to CFW but increased filamentation (18). The conditional null mutation of GPI19 led to reduced surface GPI anchor levels, cell wall biogenesis aberrations (aggregation), and increased filamentation, but not increased CFW sensitivity (67).…”
Section: Discussionmentioning
confidence: 99%
“…The GPI7-null mutant showed reduced hyphal growth on solid media, increased sensitivity to Calcofluor white (CFW), reduced virulence in mice, and lytic action of macrophages (50). The PGA1 mutant showed reduced adherence and biofilm formation and increased sensitivity to CFW but increased filamentation (18). The conditional null mutation of GPI19 led to reduced surface GPI anchor levels, cell wall biogenesis aberrations (aggregation), and increased filamentation, but not increased CFW sensitivity (67).…”
Section: Discussionmentioning
confidence: 99%
“…Literature data [12] point out that there are transcriptional factors (other than Cph1 and Efg1) involved in regulation of both [7], the EED1 gene seems to encode a key regulator of hyphal growth and other virulence factors like SAP5 which is hyphaeassociated and up-regulated during RHE infections and patient samples. Previous studies identified another key transcriptional factor, Ume6 which is necessary for the extension of germ tubes into hyphae as well as other genes' expression [35,36,39]. Taken together, it should be noted that SAP4 may be regulated by neither Efg1 nor Cph1 and other transcriptional factors may regulate this gene expression under human serum influence [3,11,12].…”
Section: Discussionmentioning
confidence: 89%
“…Taken together, it should be noted that SAP4 may be regulated by neither Efg1 nor Cph1 and other transcriptional factors may regulate this gene expression under human serum influence [3,11,12]. Moreover, the proteinase encoded by this gene, if translated, may be associated with C. albicans infection and is quite different from laboratory culture conditions [35,41].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The RM 1000 parental strain was transformed with plasmid p ABSK2 to restore uridine prototrophy as described previously [16, 17]. Successful transformants were selected on selective YNB medium supplemented with the appropriate amino acids.…”
Section: Methodsmentioning
confidence: 99%